“Top-down and bottom-up processing of knowledge in language learning” (Zien Journal of Social Sciences and Humanities, 2022)
Top-down and bottom-up are well -known approaches in language learning as well as teaching.This article is aimed at focusing on particular features of these two processes and how scientists deal withteaching L2 for learners. Besides that, it covers similarities and differences of them, the ways that learnersacquire knowledge effectively and provide some examples